Liposome-based transfection enhances RNAi and CRISPR-mediated mutagenesis in non-model nematode systems - Adams, Sally (Sci Rep, 2019)
Nematodes belong to one of the most diverse animal phyla. However, functional genomic studies in nematodes, other than in a few species, have often been limited in their reliability and success. Here we report that by combining liposome-based technology with microinjection, we were able to establish a wide range of genomic techniques in the newly described nematode genus Auanema. The method also allowed heritable changes in dauer larvae of Auanema, despite the immaturity of the gonad at the time of the microinjection. As proof of concept for potential functional studies in other nematode species, we also induced RNAi in the free-living nematode Pristionchus pacificus and targeted the human parasite Strongyloides stercoralis.